2018
DOI: 10.4132/jptm.2018.07.09
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Placental Inflammation as a Risk Factor of Severe Retinopathy of Prematurity

Abstract: BackgroundChronic placental inflammation (CPI) has been implicated in the pathogenesis of diseases in premature infants, whereas retinopathy of prematurity (ROP) is a major complication primarily affecting preterm and very low-birth-weight (VLBW) infants. This study aims to investigate the association between CPI and ROP in VLBW infants.MethodsWe performed a retrospective review of clinical records of VLBW infants born between 2013 and 2016. Placental pathology findings including CPI cases were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Furthermore, chronic inflammation as a result of MO induces dysregulation of placental angiogenesis (Kim et al . ). On the other hand, exercise can suppress inflammation as a result of obesity (Antunes et al .…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, chronic inflammation as a result of MO induces dysregulation of placental angiogenesis (Kim et al . ). On the other hand, exercise can suppress inflammation as a result of obesity (Antunes et al .…”
Section: Discussionmentioning
confidence: 97%
“…Neonatal early onset sepsis is secondary to intrauterine infection in most cases, which may increase the risk for the development ROP. [56,57] Moreover, infants with intrauterine infection after birth always have a worse respiratory condition, which is typically treated with a higher concentration of oxygen and more advanced mechanical ventilation (such as invasive mechanical ventilation), which also increases the likelihood of ROP occurrence. [58,59] On the contrary, we found that the association of fungal sepsis with ROP was stronger than that of bacterial sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to oxygen administration [ 14 , 15 ], GA and BW represent major risk factors for ROP and are at the core of most ROP screening guides [ 16 , 17 ]. Studies on ROP physiopathology have suggested the possible implication of other factors, namely, maternal, such as preeclampsia and chorioamnionitis; prenatal; perinatal; demographic; genetic; and factors related to medical treatment and nutrition [ 16 , 18 ]. In a recent study, it has been demonstrated that prenatal steroid administration, GA, artificial ventilation, and respiratory distress syndrome (RDS) are correlated with ROP and bronchopulmonary dysplasia, intraventricular hemorrhage, and periventricular leukomalacia and the number of red cell concentrate transfusions are significantly correlated with ROP [ 2 ].…”
Section: Introductionmentioning
confidence: 99%